Garcinone-E exhibits anticancer effects in HeLa human cervical carcinoma cells mediated via programmed cell death, cell cycle arrest and suppression of cell migration and invasion - Yang, Linli (AMB Express, 2020)
Xanthones are an important class of natural compounds bearing huge bioactivity profiles. Garcinone-E is one among most active xanthones showing potential anticancer activity against various human cancer cell lines. Therefore, the current study was performed to explore the anticancer potency of naturally occurring garcinone-E xanthone against human HeLa cervical cancer cells. The underlying mechanism of action was also tried to be explored via testifying its induction of programmed cell death, arrest of cell cycle, suppression of cell migration, cell invasion and cell adhesion. MTT assay was implemented to estimate the viability of HeLa cells after garcinone-E exposure and clonogenic assay was used to analyze the effect on clonogenic potential. Acridine orange/ethidium bromine (AO/EB) staining assay was performed for monitoring of programmed cell death along with western blotting. Flow cytometric studies were carried out to analyze cell cycle check points. Transwell chambers assays were carried out for studying the impact of garcinone-E on migration and invasion potency of HeLa cells. Western blotting was used to study the expressions of apoptosis linked proteins in HeLa cells. Results indicated that garcinone-E remarkably decreased the viability to minimum in HeLa cells in both dose and time-reliant manner. The clonogenic capacity of HeLa cells was efficiently reduced by garcinone exposure. AO/EB staining showed that the anti-viability action of garcinone-E was apoptosis allied which was supported by western blotting as well. The cell cycle check points study indicated cell cycle arrest at G2/M-phase. HeLa cell migration and invasion were reduced efficiently after being subjected to garcinone-E treatment in a dose reliant fashion. In conclusion, garcinone-E has a remarkable potential to act as anti-cervical cancer chemopreventive provided further in vivo studies are required.